Care and challenges experienced by parents in the Neonatal Intensive Care Unit: Integrative review (Research, Society and Development, 2024)
Objective: to characterize the care and challenges experienced by parents when dealing with their child admitted to the NICU, performing the Kangaroo Mother Care, in its first stage. Method: this is an integrative review with searches carried out in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Science Direct, SCOPUS and Web of Science. After eligibility criteria, the final sample consisted of 34 articles, resulting in eight main themes. Results: the themes found were: Antagonistic feelings; Breastfeeding; Neonatal Intensive Care Unit Environment; Relationship with the healthcare team and participation in care; Kangaroo Method; Support networks; Maternal role x Paternal role. Conclusion: diversity was noticed in the approach to parents' experiences in the Neonatal Intensive Care Unit. There was unanimity on the importance of early bonding between parents and children, requiring greater sensitivity from health professionals in the early integration between both. Contributions to practice: based on the results, it was possible to prepare and validate the practical guide with a view to helping parents during hospitalization in the Neonatal Intensive Care Unit.